Simultaneously improving the corrosion resistance and strength of magnesium via low levels of Zn and Ge additions. (1st August 2018) - Liu, R.L.; Zeng, Z.R.; Scully, J.R.; Williams, G.; Birbilis, N.
Highlights: A new class of ternary Mg-Zn-Ge alloys presented, with excellent balance of corrosion resistance and strength. Metallurgical additions of Ge to Mg-Zn alloys were successfully able to decreasing the net cathodic (HER) kinetics. Mg-Zn-Ge alloys revealed low mass loss and hydrogen evolution relative to Mg-alloys to date. AESEC testing revealed that combined Zn and Ge alloying additions reduced the partial anodic dissolution rate of Mg. Abstract: Satisfactory corrosion resistance remains an issue in the widespread implementation of magnesium (Mg). The use of alloying to improve mechanical properties of Mg generally accelerates corrosion due to microstructural heterogeneity. However, recent works have revealed that additions of elements serving as 'cathodic poisons' such as arsenic (As) and germanium (Ge) can reduce cathodic reaction rates and suppress cathodic activation - imparting corrosion resistance. The effect of Ge was translated into a ternary (and mechanically relevant) Mg-alloy system for the first time, revealing an alloy system with a balance of properties, and low rate of corrosion relative to Mg-alloys to date.